Akibat Hukum Terjadinya Salah Transfer Dana Perbankan - Anak Agung Bagus Ari Satya Dharma; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
In this era of globalization, everyone is certainly no stranger to fund transfer activities. Transfer of funds is very helpful in community activities, but with the convenience of the facilities provided by the bank, of course there are risks, such as errors in transferring funds. The purpose of this research is to determine the legal knowledge of banking fund transfers and to discuss the legal consequences of errors in bank fund transfers. This research is a normative legal research supported by primary and secondary legal materials. The data collection technique in this research is to record and document. The data analysis technique is to examine books, literature and electronic media related to this research. The results of the reserach explain that UUTD no. 3 of 2011 in Article 1 point 1 regulates the definition of transfer or transfer of funds, namely an activity of transferring funds of a certain amount by the original sender to the recipient who has been mentioned in the order for the transfer of funds until it is received. And based on Article 1360 of the Civil Code, which states: "Whoever knowingly or not, receives something that does not have to be paid to him, must return it to the person who gave it". So that according to civil law, a person is obliged to return funds that are not his right from the results of an error in transferring funds that occur with a note that the bank must be able to clearly prove that the funds are not intended for the person concerned.